Immune responses and inorganic ion transport regulations of Epinephelus coioides in response to L321_RS13075 gene of Pseudomonas plecoglossicida. Issue 120 (January 2022) - Qi, Weilu; Gao, Qiancheng; Tian, Jing; Wu, Bi; Lin, Miaozhen; Qi, Shanni; Yan, Qingpi; Huang, Lixing
Abstract: Pseudomonas plecoglossicida is a well-known pathogen of viscera granulomas disease in fish, which has led to severe economic losses. In our previous study, L321_RS13075 was predicted to be a key virulence gene of P. plecoglossicida during the host-pathogen interaction with Epinephelus coioides . To investigate the role of L321_RS13075 in the regulation of virulence in P. plecoglossicida, a L321_RS13075 knock-down strain was constructed. And a significant reduction in the ability of colonization, intracellular survival, motility, biofilm formation, and adhesion was detected in the L321_RS13075 knock-down strain. Compared with the wild-type strain, the silence of L321_RS13075 in P. plecoglossicida resulted in a significant change in the transcriptome of infected Epinephelus coioides ( E. coioides ). Results of COG and GO analysis on E. coioides showed that genes related to immune responses and inorganic ion transport were significantly affected by L321_RS13075 of P. plecoglossicida . Meanwhile, the interactions of the genes related to immune responses and inorganic ion transport were predicted, and the important hub genes were identified. Taken together, the results indicated that L321_RS13075 was a virulent gene of P. plecoglossicida, which significantly affected the immune responses and inorganic ion transport in E. coioides . Highlights: ● Pseudomonas plecoglossicida is a temperature dependent bacterial pathogen in fish ● L321_RS13075 is critical for P. plecoglossicida virulence ● L321_RS13075 significantly affected the immune responses in E. coioides ● L321_RS13075 significantly affected the inorganic ion transport in E. coioides